Peran Kepemimpinan Kepala Sekolah Dalam Inovasi Lembaga Pendidikan - Tsani Abdallah, Muhammad; Khoirur Roziqin , Muhamad; Fodhi , Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to analyze the role of principal leadership in encouraging innovation in educational institutions, especially in SMP Negeri 2 Peterongan. Educational innovation is an important factor in improving the quality of learning and adapting schools to the development of the times. In this context, the principal as a leader plays an active role in creating an atmosphere that supports the implementation of innovation in all aspects of the school, from curriculum development, technology-based learning, to self-development programs for teachers and students. The method used in this study is a qualitative approach with a case study. Data collection was carried out through in-depth interviews, observations, and documentation involving the principal, teachers, and school staff. The results of the study indicate that the principal at SMP Negeri 2 Peterongan applies transformational leadership that supports the creation of various innovations. Communicative, open, and collaborative leadership helps motivate teachers to innovate in learning and school management. In addition, the principal also has an important role in creating an innovative school culture by encouraging the active involvement of all related parties in designing and implementing new programs. This research is expected to contribute to the development of an effective leadership model in improving educational innovation at the secondary school level, as well as providing insight for other principals in implementing policies that support innovation in schools.